2009
DOI: 10.1002/ajmg.a.32765
|View full text |Cite
|
Sign up to set email alerts
|

Connexin mutations in Brazilian patients with skin disorders with or without hearing loss

Abstract: The connexins are a family of proteins whose major function is as part of the gap junctions of cell-to-cell channels. They are expressed in several tissues including brain, skin, and cochlea. Mutations in connexin genes play a major role in non-syndromic sensorineural deafness, but have been also described in individuals with variable dermatological features. In recent years, many genes responsible for hereditary skin diseases have been discovered. These genes may encode different proteins that participate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…However, c.758C > T is a known change that is not considered to be pathogenic. It has been reported before in both cases and controls in various studies on GJA1 (Alexandrino et al, 2009;Paznekas et al, 2009;Kooshavar et al, 2012;Van Norstrand et al, 2012), but has been suggested to modify disease severity in certain cases (Cella et al, 2006).…”
Section: Genetic Markers For Nonsyndromic Deafnessmentioning
confidence: 78%
“…However, c.758C > T is a known change that is not considered to be pathogenic. It has been reported before in both cases and controls in various studies on GJA1 (Alexandrino et al, 2009;Paznekas et al, 2009;Kooshavar et al, 2012;Van Norstrand et al, 2012), but has been suggested to modify disease severity in certain cases (Cella et al, 2006).…”
Section: Genetic Markers For Nonsyndromic Deafnessmentioning
confidence: 78%
“…In another case, the E42K mutation in Cx43 was found to be associated with sudden infant death syndrome which is thought to be linked to cardiac arrhythmias [69]. Finally, in a few very rare cases, reports have shown that GJA1 mutations can be associated with hearing loss and skin disorders with little or no evidence of ODDD [70–72].…”
Section: The Cx43 Mutation Compositementioning
confidence: 99%
“…The epidermis is primarily composed of keratinocytes, which temporally and spatially express as many as 10 different connexins, depending on their degree of differentiation (2,6). In addition, the importance of gap junctions in epidermal differentiation is supported by the discovery that mutations in gap junction proteins are the underlying cause of several inherited skin diseases (2,11). In rat epidermis, Cx26, Cx31, Cx31.1, Cx37, and Cx43 were demonstrated by immunofluorescence and Northern blot analysis (8), and Cx26, Cx30, Cx30.3, Cx31, Cx31.1, Cx32, Cx37, Cx40, Cx43, and Cx45 mRNAs have been detected in human epidermis (10), although Cx32 expression was low.…”
Section: Discussionmentioning
confidence: 99%
“…With SuperScript reverse transcriptase (GIBCO-BRL, NY, USA), complementary DNA was synthesized from 1 µg of total RNA in the presence of oligo (dT) [8][9][10][11][12] hexamer (Amersham Pharmacia Biotech, Buckinghamshire, UK) in a reaction volume of 20 µl at 37°C for 60 min. One microliter of cDNA solution was amplified with Ex Taq polymerase (Takara, Tokyo, Japan) in a volume of 12.5 µl, using each set of 20-µM primers.…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation